Implicit Understandings in Channels of Distribution - Shugan, Steven M. (Management Science, 1985)
Formal agreements can be used to achieve coordination among channel members. These agreements work by exerting explicit control over the members who make the agreements. However, implicit understandings can be used as a partial substitute for more formal agreements. In this paper, we show that implicit understandings can develop as channel members learn about each other's behavior. We show that … This learning leads to the use of the implicit influence each channel member has over the other's behavior. The learning leading to an implicit understanding requires some form of experimentation or historical observation. This learning results in an oscillating retail price. When only one channel member learns the other's behavior, both channel members obtain greater profits than when neither member learns, and both channel members obtain less profits than when both members learn. However, the member who does not learn obtains more profits than the member who learns. We also show that … Implicit understandings result in greater channel profits than in their absence. Implicit understandings cannot fully substitute for an explicit contract. Implicit understandings result in a retail price which is higher than the price resulting from an explicit contract but lower than the price resulting in the absence of an implicit understanding. Implicit understandings develop as channel members learn each other's behavior. We demonstrate that the form of learning discussed in this paper is consistent with a somewhat general demand function. Finally, the paper provides some examples of both symmetrical learning, where both channel members learn at the same speed and asymmetrical learning where channel members learn at different speeds.